Education for intercultural citizenship: Concepts and comparisons - Alred, Geof; Byram, Michael; Fleming, Michael (Michael P.) (Languages for intercultural communication and education, 2006)
This book presents a vision of education for citizenship, which takes as its starting point an account of what it means to be intercultural. Theory and concepts of interculturality are applied to citizenship education in order to extend its meaning and significance within and beyond the nation state. The book advances a concept of intercultural citizenship which is sensitive to complexities of identity and diversity and, through international case studies, analyses the degree to which intercultural citizenship is present or emergent in contemporary education systems It provides a statement of ‘axioms and characteristics’ of education for intercultural citizenship to act both as a framework for planning education for intercultural citizenship and as criteria for evaluating the degree of intercultural citizenship education already present in existing education systems. The book will be of interest to those currently working in intercultural education as well as those who work in education for citizenship.